Microscopic Analysis of Temperature Effects on Surface Colonization and Biofilm Morphology of Salmonella enterica - Zachariah Vice; You Zhou; Sapna Chitlapilly Dass; Rong Wang (Foods)
Salmonella enterica represents a diverse group of pathogens commonly associated with food contamination including red meat. Even though pre- and post-harvest cleaning and sanitization procedures are widely implemented at meat processing plants to mitigate the hazard, S. enterica cells may escape the process by colonizing, on contact, surfaces in the form of a biofilm that functions as an aggregated microbial community to facilitate mutual protection, antimicrobial resistance, proliferation and dissemination. Biofilm development is a complex process that can be affected by a variety of factors including environmental temperature. We developed methods using scanning electron microscopy and confocal microscopy with a novel image analysis software tool to investigate the temperature influence on S. enterica cell colonization and biofilm formation by directly visualizing and comparing the biofilm matrix’s morphological differences under various temperatures. Cocktails of S. enterica strains belonging to serovars, commonly isolated from meat samples, were applied to develop biofilms on a stainless steel surface at 7, 15, or 37 °C. Results of the microscopy analysis showed that as temperature increased, better-defined biofilm structures with extracellular polymeric structures (EPS) could be identified. However, S. enterica colonization and aggregated bacterial biomass were clearly observed at the low temperature (7 °C) as well. These results demonstrate that the environmental temperature significantly contributes to S. enterica biofilm formation as the higher temperatures encourage bacterial active proliferation and biofilm maturation leading to the development of well-pronounced structures, while the lower temperature may promote cell attachment but, meanwhile, limit the EPS biosynthesis and biofilm maturation. Our study indicates that the mature S. enterica biofilms formed under favorable conditions may protect the pathogens with the well-developed 3-demensional (3D) structure against routine treatment. Furthermore, the low temperatures commonly maintained at meat plants are not able to effectively prevent S. enterica colonization and biofilm formation since at such temperatures there could still be colonized biomass that can contaminate the products. Therefore, the temperature effect on pathogen colonization and biofilm development should be taken into consideration while evaluating hygiene standards and sanitization procedures at the processing facilities.